Implementation of the Development of Islamic Religious Education Teaching Materials Based on Project Based Learning to Strengthen Religious Moderation in Students at SDN Pager 02 Purwosari - Rokhimah, Siti Ainur; Marzuki, Ahmad (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to develop Islamic Religious Education (PAI) teaching materials based on Project Based Learning (PjBL) for third-grade students at SDN Pager 02 Purwosari as an effort to enhance learning engagement and instill values of religious moderation from an early age. Addressing the issues of low student participation in project-based learning and the limited availability of digital learning resources, the teaching materials were developed using the ADDIE model by integrating interactive media, staged project tasks, and contextual approaches suited to students’ cognitive development. Expert validation showed the materials were feasible for use, and classroom implementation demonstrated improvements in student activity, creativity, and understanding of religious and social values. Therefore, PjBL-based teaching materials are not only effective in supporting academic achievement but also in shaping students’ character to be more tolerant, collaborative, and independent.